Creating Exciting Content: A Descriptive Study of Pixbox's Digital Marketing Strategies on Social Media - Simabur, Lisda Ariani; Herlina, Rita; Wiradharma, Gunawan (Universitas Ahmad Dahlan, 2023)
Many companies have adapted their marketing strategies to focus on digital media to overcome the limitations of face-to-face communication. Pixbox, an Indonesian local shipping company, has created brand awareness through digital marketing, including social media platforms, to attract customers and promote their services. This study aims to determine how the Pixbox creative team creates digital marketing content on social media. The research used a descriptive qualitative approach, collecting data through interviews and analyzing them using qualitative methods. The study focused on the Pixbox marketing content creator team and their social media activities, using purposive sampling to select participants and qualitative data analysis techniques to analyze the data. This study indicated that in creating exciting content, the content creator team of Pixbox carried out three stages, namely the pre-production stage, trying to plan content by thinking about how the purpose of the content will be, the production stage as a stage of content creation strategy as well as publishing it. The post-production stage, as the content evaluation stage, shows that the achievement of content creation on social media has an impact on increasing Pixbox brand awareness/customers, which is targeted at young entrepreneurs. Pixbox’s content creator team creates exciting marketing content in three stages: pre-production, production, and post-production, successfully increasing brand awareness and customer orders. Suggestions for improvement include better planning and research in the pre-production stage, exploring other social media platforms, and constantly evaluating content creation.